Kinetics and reaction pathways of total acid number reduction of cyclopentane carboxylic acid using subcritical methanol - Mandal, P.C. (De Gruyter Open Ltd, 2016)
Cyclopentane carboxylic acid (CPCA) is a model compound of Naphthenic acids (NAs). This objective of this paper is to discover total acid number (TAN) reduction kinetics and pathways of the reaction between CAPA and subcritical methanol (SubC-MeOH). The experiments were carried out in an autoclave reactor at temperatures of 180-220Â°C, a methanol partial pressure (MPP) of 3 MPa, reaction times of 0-30 min and CPCA initial gas phase concentrations of 0.016-0.04 g/mL. TAN content of the samples were analyzed using ASTM D 974 techniques. The reaction products were identified and quantified with the help of GC/MS and GC-FID respectively. Experimental results reveal that TAN removal kinetics followed first order kinetics with an activation energy of 13.97 kcal/mol and a pre-exponential factor of 174.21 s-1. Subcritical methanol is able to reduce TAN of CPCA decomposing CPCA into new compounds such as cyclopentane, formaldehyde, methyl acetate and 3-pentanol. Â© by Pradip C. Mandal 2016.